(STUDI PADA TERMINAL TIPE A ISIMU BPTD WILAYAH XXI PROVINSI GORONTALO) - Nirmala A. Sahi; Dikson Junus; Muten Nuna; Amirudin Paramata (Jurnal Dialektika Politik, 2024)
Implementation of the principles of Good Governance, where the state is the party that plays the most important role in realizing these principles. The implementation of Good Governance is the main prerequisite for realizing the aspirations of the community in achieving the goals and aspirations of the nation and the State, this cannot be separated from the application of the principles of good governance at the Isimu BPTD Type A Terminal in Region XXI of Gorontalo Province. This research was conducted to determine the implementation of good governance in the management of the Type A Isimu BPTD Terminal Region XXI Gorontalo Province. This research uses a qualitative descriptive method with an analytical method, namely research that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this research indicate that the implementation of good governance in the governance of the Type A Isimu BPTD Terminal Region XXI Gorontalo Province has not been fully implemented optimally. This can be seen from several indicators, namely: planning that has not been optimal, namely related to track routes and output as the final result, organization that has not been maximized, namely related to the arrangement of bus parking and track routes, implementation of activities that still need to be improved, and supervision that has not been carried out optimally. The recommendation of this research is that the Land Transportation Management Center Region XXI Gorontalo Province through the Isimu Type A Terminal service unit should: 1) further maximize the terminal work plan, 2) further maximize terminal management, by continuing to improve security, cleanliness and order in the terminal, 3) need to maximize the function of the Terminal, and 4) need to increase supervision over the use of the terminal and supporting facilities according to their intended purpose, especially vehicle parking areas that are not yet neatly arranged.